Konstruksi Gender dalam Media Islam dan Sekuler: Analisis Framing Berita Poligami, Pernikahan Dini, dan KDRT - Umi Halwati; Imam Alfi; Johar Arifin; Retno Sirnopati (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2022)
This article is a research report focusing on the construc–tion of Kompas and Republika's news coverage regarding gender-related issues such as polygamy, domestic violence, and early marriage. Zondhang Pan and Gerald M. Kosicki's framing analysis was applied to analyse six news articles published by Kompas and Republika in 2021. The findings illustrate that both Kompas and Republika tend to construct gender discourse to mainstream gender equality in order to